2013
DOI: 10.1002/etc.2228
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity of pyraclostrobin and trifloxystrobin to Hyalella azteca

Abstract: Fungicide application rates on row crop agriculture have increased across the United States, and subsequently, contamination of adjacent wetlands can occur through spray drift or field runoff. To investigate fungicide toxicity, Hyalella azteca amphipods were exposed to 2 fungicide formulations, Headline and Stratego, and their active strobilurin ingredients, pyraclostrobin and trifloxystrobin. Water-only exposures resulted in similar median lethal concentration (LC50; 20-25 µg/L) values for formulations and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 24 publications
0
55
1
Order By: Relevance
“…Available chronic toxicities of boscalid and myclobutanil (21-d no-observed-effect concentration [NOEC]) on Daphnia magna were similar, at 1 mg/L and 1.3 mg/L, respectively [11], and much lower compared with the chronic toxicity of these fungicides on A. subtenuis as observed in the present study. The amphipod Hyalella azteca, for example, was also reported to be more sensitive to the fungicide trifloxystrobin (96-h median lethal concentration [LC50] ¼ 24.7 mg/L) [46] than D. magna (96-h LC50 ¼ 530 mg/L) [8]. This is in agreement with results observed for other fungicides, such as tebuconazole; Sancho et al [13] found that survivorship of D. magna did not decrease after exposure to 1.14 mg/L tebuconazole over 14 d but was significantly reduced by 6% compared with controls after 21 d. Species sensitivity could also be a reason for the different toxic effects between studies.…”
Section: Survivalmentioning
confidence: 99%
“…Available chronic toxicities of boscalid and myclobutanil (21-d no-observed-effect concentration [NOEC]) on Daphnia magna were similar, at 1 mg/L and 1.3 mg/L, respectively [11], and much lower compared with the chronic toxicity of these fungicides on A. subtenuis as observed in the present study. The amphipod Hyalella azteca, for example, was also reported to be more sensitive to the fungicide trifloxystrobin (96-h median lethal concentration [LC50] ¼ 24.7 mg/L) [46] than D. magna (96-h LC50 ¼ 530 mg/L) [8]. This is in agreement with results observed for other fungicides, such as tebuconazole; Sancho et al [13] found that survivorship of D. magna did not decrease after exposure to 1.14 mg/L tebuconazole over 14 d but was significantly reduced by 6% compared with controls after 21 d. Species sensitivity could also be a reason for the different toxic effects between studies.…”
Section: Survivalmentioning
confidence: 99%
“…These findings, and the work of others, indicate that the increased use of fungicides in the United States [14,15], and the expected increase in use globally [55], are likely to pose significant risks to leaf-derived nutrient cycling in streams. These findings, and the work of others, indicate that the increased use of fungicides in the United States [14,15], and the expected increase in use globally [55], are likely to pose significant risks to leaf-derived nutrient cycling in streams.…”
Section: Fungicide Effects On Macroinvertebrates: Tusmentioning
confidence: 90%
“…Although boscalid is considered moderately to highly toxic to aquatic invertebrates [50], the high concentration in the present study (24 mg/L) falls well below the 48-h LC50 (5300 mg/L) and the 21-d chronic NOEC (1300 mg/L) of boscalid for D. magna (Table 1). Indeed, based on the 96-h LC10 of 12 mg/L pyraclostrobin for H. azteca [14], we might expect to see reduced survival of H. azteca exposed to 8.4 mg/L pyraclostrobin for 14 d in the PRISTINE treatment. Indeed, based on the 96-h LC10 of 12 mg/L pyraclostrobin for H. azteca [14], we might expect to see reduced survival of H. azteca exposed to 8.4 mg/L pyraclostrobin for 14 d in the PRISTINE treatment.…”
Section: Fungicide Effects On H Azteca Survival and Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus calculated LC50s were based solely on time‐weighted average (Equation ) pyraclostrobin concentrations. Time‐weighted average water concentrations ( C TWA ) were achieved by fitting a first‐order exponential decay function through average water concentrations measured over time and taking the average of the curve, so that CTWA=abffalse(xfalse)dx(ba) where a = 0 h, b = 96 h, and f ( x ) = first‐order exponential decay function . Differences in H. trivolvis mortalities and bioconcentration factors (BCFs) were determined with IBM SPSS Statistics Data Editor.…”
Section: Methodsmentioning
confidence: 99%